Prosedur Pemberian Kredit Kepada Golongan Berpenghasilan Tetap dan Kredit KUR Di PT. Bank Rakyat Indonesia (Persero) Tbk. Unit Simalingkar Medan - Damanik, Cindy Theresia M.M; Sitorus, Friska Darnawaty (Jurnal Ekonomi Bisnis Digital, 2022)
The procedure for granting credit is important in determining eligibility and benchmarks in making a decision whether the debtor is eligible or not to receive credit provided by the Bank. Not only that, the procedure for granting credit is also a system and procedure that has been established by banks to facilitate banks in carrying out their work as distributors of funds to the public in the form of loans in a systematic and neat and structured manner so as to make it easier for banks to assess prospects in offering credit. The purpose of this discussion is to find out the procedure for providing multipurpose loans, both fixed loans and credit Usaha Rakyat(KUR) at PT BANK BRI (Persero) Tbk Simalingkar Unit. The data collection technique used is qualitative data obtained from interviews with several staff and customers at Bank BRI Simalingkar unit. Data was collected by observation and interviews. The results showed that PT Bank Rakyat Indonesia Simalingkar unit had implemented a credit granting procedure system in accordance with standard operating procedures (SOP); credit stage, credit examination/analysis stage, credit decision granting stage, credit card first stage, and credit development stage.